Data Models Research in Accounting: An Evaluation of Wholesale Distribution Software - Weber, Ron (The Accounting Review, 1986)
[The data definitions in the order entry modules of 12 wholesale distribution software packages were studied to determine whether (a) their high-level semantics complied with McCarthy's [1982] REA accounting model; (b) their detailed semantics manifested a common underlying accounting model; (c) their semantics could be modeled adequately using the entity-relationship modeling technique; and (d) their record structures followed the prescriptions of normalization theory. The results indicate that the major elements of the REA model are incorporated in the packages. However, they differ semantically in several important areas that could not be detected by the REA model because it is too general. Use of the entity-relationship modeling technique to represent the semantics of the packages was relatively straightforward. In terms of record structures, the packages conform with the prescriptions of normalization theory to a large extent, although there are still several violations of normal form.]